Surveillance of Pediatric Cardiac Surgical Outcome Using Risk Stratifications at a Tertiary Care Center in Thailand - Chodchanok Vijarnsorn; Duangmanee Laohaprasitiporn; Kritvikrom Durongpisitkul; Prakul Chantong; Jarupim Soongswang; Paweena Cheungsomprasong; Apichart Nana; Somchai Sriyoschati; Thawon Subtaweesin; Punnarerk Thongcharoen; Ungkab Prakanrattana; Jiraporn Krobprachya; et al. (Cardiology Research and Practice)
Objectives. To determine in-hospital mortality and complications of cardiac surgery in pediatric patients and identify predictors of hospital mortality. Methods. Records of pediatric patients who had undergone cardiac surgery in 2005 were reviewed retrospectively. The risk adjustment for congenital heart surgery (RACHS-1) method, the Aristotle basic complexity score (ABC score), and the Society of Thoracic Surgeons and the European Association for Cardiothoracic Surgery Mortality score (STS-EACTS score) were used as measures. Potential predictors were analyzed by risk analysis. Results. 230 pediatric patients had undergone congenital cardiac surgery. Overall, the mortality discharge was 6.1%. From the ROC curve of the RACHS-1, the ABC level, and the STS-EACTS categories, the validities were determined to be 0.78, 0.74, and 0.67, respectively. Mortality risks were found at the high complexity levels of the three tools, bypass time >85 min, and cross clamp time >60 min. Common morbidities were postoperative pyrexia, bleeding, and pleural effusion. Conclusions. Overall mortality and morbidities were 6.1%. The RACHS-1 method, ABC score, and STS-EACTS score were helpful for risk stratification.